(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The participation of the Research Team in previous projects, sponsored by the Universidad del Salvador (USAL), related to the increase of efficiency / productivity / quality and its tools applied to the productive sector, has allowed to corroborate that the efforts in the Improvement Programs in the SME sector, decline considerably before reaching maturity, both in the application of quality management tools, as in the use of non-quality cost measurement techniques We have identified its causes, due in part to the lack of a plan that establishes what, how and where to measure to appreciate the results; and in part, to the disparate linkage (cause/effect) between the initiatives undertaken and the objectives pursued. For this reason, it was proposed to study, define and formulate an efficient model of Key Performance Indicators (KPI) that allows verifying the progress of Continuous Improvement (CI) processes with a focus on the SME field, both in the production of goods and services. The presentation considers the incorporation of performance measurement schemes to the "Model of the 5 Phases for the implementation of Lean Six Sigma adapted to the SME reality" (presented at COINI 2021), a model that is based on the determination and compliance of a set of Critical Success Factors (CSF) and its application sequence. The literature on this subject was analyzed, determining its applicability to our SME reality, and the modeling was defined to identify those KPIs that are easier to obtain and have the greatest impact on the objectives pursued, both indicators of final effect on the result to be achieved, and causes to obtain it.